Chemotactic behaviour of Escherichia coli at high cell density - Remy Colin (Nature Portfolio, 2019)
Swimming bacteria perform collective motion at high cell density, yet it is unclear how this behaviour affects their ability to follow substance gradients in the environment. Here, Colin et al. address this question by studying motion of Escherichia coli in controlled chemical gradients.